Exercise-based cardiac rehabilitation for patients with atrial fibrillation receiving catheter ablation: protocol for a feasibility randomised controlled trial (RCT) with embedded process evaluation - Gregory Y H Lip; Helen Jones; Mark T Mills; Dhiraj Gupta; Lawrence Foweather; Benjamin JR Buckley; Charlotte Fitzhugh (BMJ Open)
Introduction Atrial fibrillation (AF) affects approximately 2.5% of the UK population, with a risk of 1 in 3–5 individuals after the age of 45 years. The global prevalence has risen sharply in the past two decades, from 33.3 million to 59 million individuals living with AF, and is associated with stroke, heart failure and mortality. Catheter ablation is commonly used for symptomatic patients to restore normal rhythm. A recent Cochrane review of randomised clinical trials (RCTs) has demonstrated that exercise training may induce positive effects on AF burden, AF severity, exercise capacity, and quality of life. The aim was therefore to investigate the feasibility of delivering exercise-based cardiac rehabilitation for patients with AF receiving catheter ablation within usual care in the UK.Methods and analysis A two-armed feasibility RCT with embedded process evaluation will be undertaken as a phased programme of work. Patients on a waiting list for catheter ablation will be offered a referral to cardiac rehabilitation. The intervention consists of supervised exercise sessions run by a clinical exercise physiologist and psychoeducation sessions. The trial (n=60) will involve one National Health Service (NHS) research site enrolling patients to assess intervention and study design processes. Primary outcomes are recruitment rate, adherence to exercise-based cardiac rehabilitation and loss to follow-up. Semistructured interviews and focus groups with patients and clinicians will be used to gather data on the acceptability of the intervention and study procedures. Secondary outcome measures will be taken at baseline (pre-intervention), post-intervention and at 6-month follow-up and will consist of AF burden, AF recurrence, quality of life, exercise capacity measured by peak oxygen consumption and echocardiographic parameters.Ethics and dissemination The trial was approved in the UK by the Northwest-Preston Research Ethics Committee (24/NW/0061; IRAS project ID: 330155). Results will be published in peer-reviewed journals and presented at national and international scientific meetings, and summaries will be communicated to participants.Trial registration number Clinicaltrials.gov identifier: NCT06401148.